v=x(25-2x)(12-2x)

Simple and best practice solution for v=x(25-2x)(12-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v=x(25-2x)(12-2x) equation:


Simplifying
v = x(25 + -2x)(12 + -2x)

Multiply (25 + -2x) * (12 + -2x)
v = x(25(12 + -2x) + -2x * (12 + -2x))
v = x((12 * 25 + -2x * 25) + -2x * (12 + -2x))
v = x((300 + -50x) + -2x * (12 + -2x))
v = x(300 + -50x + (12 * -2x + -2x * -2x))
v = x(300 + -50x + (-24x + 4x2))

Combine like terms: -50x + -24x = -74x
v = x(300 + -74x + 4x2)
v = (300 * x + -74x * x + 4x2 * x)
v = (300x + -74x2 + 4x3)

Solving
v = 300x + -74x2 + 4x3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Simplifying
v = 300x + -74x2 + 4x3

See similar equations:

| 7p-5(3+p)=7p-15-5p | | -16=4a+2a | | 16.7d+66.7=25d+-.5 | | .666(5)= | | 3.5s-7.3=-7.3+2.6s | | (2x-11)/3=4+x | | x+7/2=7 | | -8x-16=-8(2x-6) | | -16=14a+2a | | 16n+1=80 | | 5-(3-f)-5=6(3-f) | | (5x/2)=3x+5 | | (2x-11)/3=4/3+x | | 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k | | (2/3)x-(1/6)=(2/7) | | d=85t+340 |

Equations solver categories